Preparation and study of the physical and mechanical properties of asphalt-rubber mixtures (Journal of the College of Basic Education, 2022)
In this work, mixtures of sulfur-free asphalt and rubber were prepared with different mixing ratios to impose obtaining the best mixing ratios in terms of studying thermal and mechanical applications.